Improved hybrid algorithm based on GA and local search method for asymmetrical 9-level inverter - Rim Feyrouz Abdelgoui; Rachid Taleb; Abderrahim Bentaallah; Fayçal Chabni (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Selective Harmonic elimination has emerged as an in-depth research method to replace traditional PWM technology. This study demonstrates the selective harmonic elimination by using a hybrid Genetic algorithm GA and local search (GA-LS) method of a uniform asymmetric multilevel inverter called USAMI That removes the higher-order harmonics defined while maintaining the fundamental voltage needed. This new technology can be implemented at any USAMI level. For example, in this article, we plan to use USAMI at 9 levels and find the optimal switching angle to remove the 5th, 7th, and 11th harmonics.